Association between shift work and periodontal health in a representative sample of an Asian population - Dong-Hun Han; Young-Ho Khang; Kyunghee Jung-Choi; Sinye Lim (Nordic Association of Occupational Safety and Health (NOROSH), 2013)
OBJECTIVE: The association of shift work with periodontal disease is not well known. We studied the relationship between shift work and periodontitis in a representative sample of an Asian population. METHODS: Participants were 4597 full-time employees from the Fourth Korean National Health and Nutrition Examination Survey (KNHANES IV). Shifting patterns were categorized into five shifts: daytime (N=3768), evening (N=121), night (N=59), rotating (N=206), and irregular (N=443). Periodontitis was measured with the Community Periodontal Index (CPI). Confounders included age, gender, income, and education. Mediators were frequency of daily tooth brushing, regular dental check-up, smoking, alcohol consumption, diabetes, obesity, and white blood cell count. Multiple logistic regression analyses were performed to evaluate the relationship. RESULTS: The prevalence of periodontitis in the study population was 32.3%. Shift workers had an elevated odds ratio (OR) of periodontitis [OR 1.22, 95% confidence interval (95% CI) 1.01-1.48] after controlling for confounders. The magnitude of the association between shift work and periodontitis attenuated with adjustment of mediators (smoking and a marker of inflammation). In subgroup analyses, the association was significant (OR 1.42, 95% CI 1.03-1.95) among those ≥45 years. Irregular shift among those ≥45 years showed a significant association (OR 1.79, 95% CI 1.15-2.78). CONCLUSION: Findings of this cross-sectional study suggest that shift work may be associated with periodontitis. Shift workers aged ≥45 years and irregular shift workers aged ≥45 years were risk groups for periodontitis.